Mechanical behaviour of commercially pure titanium with different porosities formed by selective laser melting - Tan, Joel Jie Yao (Nanyang Technological University, 2021)
Commercially pure titanium (cp-Ti) has gained great attention in biomedical applications due to their excellent mechanical properties, biocompatibility, and chemical stability. A common additive manufacturing method known as Selective Laser Melting (SLM) is used to fabricate parts. However, this process has posted several challenges such as martensitic microstructures, undesired porosity and residual stresses which are present during this process. Experimental testing methods are usually used to identify the relations between mechanical properties and porosity fraction. However, these conventional analyses are time consuming and costly. The primary goal is to analyse the importance of part porosity with the level as low as 1%. This project identiﬁes the usage of porosity volumetric fraction and plasticity model such as Johnson Cook’s and Steinberg-Guinan to analyse the mechanical behaviour of a tensile coupon. The post yield and failure behaviour are characterized by strain hardening and damage constants, respectively, under dynamic strain rate. Ansys 2021 R1 dynamic model simulation shows the initial to final state of the part in relations to its yield strength and shear modulus. Validation was performed on experimental and simulated data for part without porosity. The experimental result achieved yield tensile strength (YTS) of 557 ± 28MPa and ultimate tensile strength (UTS) of 682 ± 14.3MPa. Finite element analysis (FEA) simulated YTS of 594 MPa and UTS of 703 MPa. 2 other samples were then modelled with porosity fraction of 1% and 2%. Sample with the lowest fraction had no significant change to the yield strength compared to perfect part but fractured at different point. The ductility also reduced gradually as the porosity fraction increased. The sample with the highest porosities had 2.8% and 0.3% dropped in ultimate tensile strength and fracture strain respectively compared to the perfect part. This project shows one of the ways to study the mechanical behaviour within part porosity in three dimensions (3D). These plasticity models have areas for improvement extended for future decision making.